Assessing and managing charismatic marine megafauna in Palau: Bumphead parrotfish (Bolbometopon muricatum) and Napoleon wrasse (Cheilinus undulatus). Issue 4 (26th February 2023) - Friedlander, Alan M.; Bukurrou, Asap; Filous, Alex; Muller Karanassos, Christina; Koike, Haruko; Koshiba, Shirley; Mereb, Geory; Nestor, Victor; Oleson, Kirsten L. L.; Olsudong, Dawnette; Oruetamor, Jay; Otto, E. Ikelau; et al.
Abstract: Bumphead parrotfish ( Bolbometopon muricatum ) and Napoleon wrasse ( Cheilinus undulatus ) are large, charismatic species with high economic and cultural value in Palau and are important for ecosystem function. As a result of intense fishing pressure, landings in Palau for both species declined dramatically in the 1990s and, in response, national legislation was enacted in 2006 that imposed a total ban on the extraction, possession, and sale of both species. In 2013 and 2021, fisheries‐independent stock assessments were conducted and found that the spawning potential ratios (SPRs) for bumphead parrotfish increased slightly from 30% to 34%. Conversely, the SPRs for Napoleon wrasse declined from 12% in 2013 to 4% in 2021. Despite the fishery being closed since 2006, these data suggest the likelihood of significant poaching, resulting in low SPR values, particularly for Napoleon wrasse. Prior to the COVID‐19 pandemic, marine tourism played a central role in the economic and social life of Palau. A willingness‐to‐pay survey found that divers would pay 1.27 million (2020 USD) more for strictly managed catches of both species, and nearly 3.00 million more if the fishery remained closed. The total market value for bumphead parrotfish peaked in 1995 at 112, 190. The peak total market value for Napoleon wrasse was 66, 434 in 2002. The welfare gain/loss for diver tourism is an order of magnitude greater than the fishery market gain/loss, and healthy marine ecosystems are essential for the post‐COVID‐19 economic recovery of Palau. However, because of the cultural importance of these species, there is a desire to manage this fishery for customary use. Opening a general subsistence harvest season is not recommended ecologically; however, the results suggest that if the SPR of bumphead parrotfish can recover to 40%, a limited quota of individuals with a total length of >95 cm could be sustained, which could be allocated via lottery. However, the fishery for Napoleon wrasse should remain closed given the extremely low SPR values and limited number of large adults in the population.